(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article describes the analysis of the causes of massive obstetric hemorrhage, treatment features, possible errors made by conservative and surgical treatment. The main causes of massive obstetric hemorrhage were postpartum atony of the uterus, detachment of a normally located placenta and placenta previa. The amount of lost blood averaged 2,410.45 ± 520.55 ml. Mistakes made during the clinical examination, surgical, conservative treatment and organizational issues led to 5 cases of maternal mortality and a deterioration in the quality of life of a woman in the study group.